Cardiovascular effects in rats after intratracheal instillation of metal welding particles. (20th January 2015) - Zheng, Wen; Antonini, James M.; Lin, Yen-Chang; Roberts, Jenny R.; Kashon, Michael L.; Castranova, Vincent; Kan, Hong
Abstract: Studies have indicated that pulmonary exposure to welding fumes can induce a series of adverse effects in the respiratory system, including infection, bronchitis, siderosis and decreased pulmonary function. Recent clinical and epidemiological studies have found that pulmonary exposure to welding fumes is also associated with a higher incidence of cardiovascular events. However, there is insufficient evidence to confirm a direct effect of welding fumes on the cardiovascular system. The present study investigated the effects of pulmonary exposure to welding fumes on the heart and the vascular system in rats. Two chemically distinct welding fumes generated from manual metal arc-hard surfacing (MMA-HS) and gas metal arc-mild steel (GMA-MS) welding were tested. Three groups of rats were instilled intratracheally with MMA-HS (2 mg/rat), GMA-MS (2 mg/rat) or saline as control once a week for seven weeks. On days 1 and 7 after the last treatment, basal cardiovascular function and the cardiovascular response to increasing doses of adrenoreceptor agonists were assessed. MMA-HS treatment reduced the basal levels of left ventricle end-systolic pressure and d P /d t max at 1 day post-treatment, and decreased d P /d t min in response to isoproterenol (ISO) at 7 days post-treatment. Unlike MMA-HS, GMA-MS only affected left ventricular end-diastolic pressure in response to ISO at 7 days post-treatment. Treatment with MMA-HS or GMA-MS did not alter heart rate and blood pressure. Our findings suggest that exposure to different welding fumes can induce different adverse effects on the cardiovascular system, and that cardiac contractility may be a sensitive indicator of cardiovascular dysfunction.